How can a decline in R* be reversed? Productivity, retirement age, and the green transition - Robert Holzmann; Andreas Breitenfellner; Wolfgang Pointner; Anna Raggl; Richard Sellner; Maria Antoinette Silgoner; Anna Stelzer; Alfred Stiglbauer (Oesterreichische Nationalbank (OeNB), 2024)
The room for maneuver of monetary policy and the relevance of the zero lower bound of nominal interest rates are largely determined by the level of and the outlook for the natural rate of interest (R*), i.e. the unobservable equilibrium interest rate that neither stimulates nor contracts the economy. Available estimates suggest that the rate has declined substantially over the last decades and even centuries. The literature on the potential drivers of this decline - both macroeconomic and financial - finds that demographic factors, real GDP trend growth, and total factor productivity have the most robust links with R*. Generally, the decline in R* was less pronounced in emerging market economies. We discuss three policies aimed at re-increasing R*, which promise to amplify the distance to the zero lower bound and therefore increase monetary policy space: (1) One promising route is boosting productivity via increased diffusion and deployment of digitalization and AI, and potentially also through transitioning toward a more climate-friendly economy. (2) Reforming the pension system, specifically raising the retirement age, could have strong transitory and even longer-term positive effects on R*. (3) The comparative advantage of the Global South is clean energy. Capital flows from the Global North to the Global South to finance investments in renewable energy may offer immense potential for unlocking productivity gains due to cheaper energy, less uncertainty, and higher returns.
Keywords: E43; E24; F21; O47; Q54; 330; interest rates; productivity; innovation; aging; climate change